African Perspectives on Ethics for Healthcare Professionals (Cham : Springer International Publishing, 2018)
This book focuses on ethical issues faced by a variety of healthcare practitioners across the Anglophone African continent. This important resource contains in-depth discussions of the most salient current ethical issues by experts in various healthcare fields. Each profession is described from both an African and a South African perspective, and thus contributes to dialogue and critical thinking around African ethics and decision-making. In this way the book provides readers with an understanding of the ethical issues at hand in various professions, including the practical implications of the ethical issues and how to address those effectively. This is a beneficial resource for all those involved in the various healthcare professions addressed in this book, including undergraduate students, lecturers, researchers and practitioners across the continent. Simply put, with the dynamic changes and challenges in healthcare across the globe and in Africa, this is an indispensable resource for healthcare practitioners. .
Chapter 1. Ethics and its Development in Africa and South Africa -- Chapter 2. Professionalism in a Changing Society- The Role of Ethics -- Chapter 2. Professionalism in a Changing Society- The Role of Ethics -- Chapter 3. Reflecting on Ethics in Occupational Therapy within a South African Context -- Chapter 4. Ethics in Occupational Therapy - African Perspective -- Chapter 5. Ethics for the Dietetic Profession - A South African Perspective -- Chapter 6. Ethics in Nutrition - An African Perspective -- Chapter 7. Ubuntu-Botho Approach to Ethics: An Invitation to Dialogue -- Chapter 8. Ethics in Psychology: An African Perspective -- Chapter 9. Ethics and Social Work - A South African Perspective -- Chapter 10. The Role of Social Work in the Provision of Healthcare in Africa -- Chapter 11. The Ethics of Care As Applied to Physiotherapy Training and Practice - A South African Perspective -- Chapter 12. Ethics in Physiotherapy Practice - An African Perspective -- Chapter 13. Ethics in Nursing - A South African Perspective -- Chapter 14. Ethics in Nursing - An African Perspective -- Chapter 15. Ethics for South African Environmental Health Practitioners -- Chapter 16. Environmental Health from an African Perspective -- Chapter 17. Ethics for Diagnostic Imaging Radiography Professionals - A South African Perspective -- Chapter 18. Ethics for Healthcare Professionals in Radiography - An Africa Perspective -- Chapter 19. Clinical Technology Ethics: Where Values and Principles Meet - A South African Perspective -- Chapter 20. Ethical Considerations in Public Health - A South African Perspective -- Chapter 21. Public Health Ethics in Research and Health Care Programs - An African Perspective -- Chapter 22. Curriculum Guidelines for Teaching Healthcare Ethics at an Undergraduate Level.
Religion and Philosophy
text file PDF
Keywords: Bioethics; Nursing ethics; Medical ethics